2017
DOI: 10.1111/ceo.12910
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens and antibiotic sensitivities in endophthalmitis

Abstract: BACKGROUND Antibiotic prophylaxis in cataract surgery is intended to minimize endophthalmitis. We describe pathogenic organisms, antibiotic sensitivities, and antibiotic prophylaxis in culture-proven endophthalmitis cases. DESIGN Retrospective consecutive case series, community-based setting. SAMPLES 215 cases of endophthalmitis after cataract surgery performed during 2007–2012 in Kaiser Permanente, California. METHODS AND MAIN OUTCOME MEASURES Descriptive analysis of isolated organisms and antibiotic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…In vitro resistance rates and susceptibility profiles in the present study are similar to reported data for bacterial isolates with specific ocular diagnoses, such as conjunctivitis,44 keratitis,12,45 and endophthalmitis 13,15,17. In a 20-year review of antibiotic resistance among 398 S .…”
Section: Discussionsupporting
confidence: 88%
“…In vitro resistance rates and susceptibility profiles in the present study are similar to reported data for bacterial isolates with specific ocular diagnoses, such as conjunctivitis,44 keratitis,12,45 and endophthalmitis 13,15,17. In a 20-year review of antibiotic resistance among 398 S .…”
Section: Discussionsupporting
confidence: 88%
“…8,9 When broken down further within gram-positives, coagulase-negative staphylococci (CoNS), which include S. epidermidis, comprise 54.6%, while Streptococcus species (20.8%), Staphylococcus aureus (10.2%), and other gram-positives (7.4%) are also frequently isolated. [9][10][11] Fungi and yeast make up 8.4% of isolates. 8 International studies have found similar results and microbiological spectrum in most countries throughout the world, including the United States (US), Australia, and European nations.…”
Section: Acute Postcataract Endophthalmitismentioning
confidence: 99%
“…Most cases of antibiotic resistance occur following the use of topical prophylaxis, and only rarely following IC prophylaxis. 10 Over the past several decades, the rates of methicillinresistant S. aureus and resistant S. pneumonia have risen significantly, with methicillin resistance seen in 34.6% to 41.6% of S. aureus endophthalmitis infections. 63 In 2015, the Antibiotic Resistance Monitoring in Ocular Microorganisms Surveillance Study 64 published susceptibility findings from isolates of the most common organisms that had been sent from clinical centers throughout the US.…”
Section: Treatment Susceptibility and Resistancementioning
confidence: 99%
“…To provide adequate Gram-negative and -positive bacterial cover in endophthalmitis cases, a currently accepted therapeutic regimen includes aminoglycosides [6]. In developing countries, aminoglycosides have become a favorable drug of choice due to their ease of access and reduced cost.…”
Section: Introductionmentioning
confidence: 99%
“…However, these treatments are not without side effects: retinal vascular infarction is commonly described after gentamicin administration, and has been noted after use of amikacin [7]. While previously noted as a rare complication, the reported frequency of macular ischemia following amikacin intravitreal injection for the treatment of endophthalmitis has increased recently [6], [8]. This report describes a case of macular ischemia following intravitreal amikacin injection.…”
Section: Introductionmentioning
confidence: 99%